Catalyst Decomposition during Olefin Metathesis Yields Isomerization‐Active Ruthenium Nanoparticles. Issue 15 (2nd August 2016) - Higman, Carolyn S.; Lanterna, Anabel E.; Marin, M. Luisa; Scaiano, Juan C.; Fogg, Deryn E.
Abstract: The front cover artwork for Issue 15/2016 is provided by the Fogg and Scaiano groups at the University of Ottawa (Canada). The image shows a well‐defined, homogeneous catalyst entering the active cycle for olefin metathesis, and exit of the decomposed catalyst in the form of ruthenium nanoparticles. See the Communication itself athttp://dx.doi.org/10.1002/cctc.201600738 . Abstract : "NPs are much more ubiquitous in organometallic chemistry than has been considered" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttp://dx.doi.org/10.1002/cctc.201600738 .